Characterization of Selective and Potent JAK1 Inhibitors Intended for the Inhaled Treatment of Asthma - Nilsson M; Rhedin M; Hendrickx R; Berglund S; Piras A; Blomgran P; Cavallin A; Collins M; Dahl G; Dekkak B; Ericsson T; Hagberg N; et al. (Dove Medical Press, 2022)
Magnus Nilsson,1 Magdalena Rhedin,2 Ramon Hendrickx,3 Susanne Berglund,1 Antonio Piras,2 Parmis Blomgran,2 Anders Cavallin,2 Mia Collins,2 Göran Dahl,4 Bilel Dekkak,5 Therese Ericsson,3 Niklas Hagberg,6 Ann Aurell Holmberg,3 Agnes Leffler,2 Anders J Lundqvist,3 Thomais Markou,5,7 James Pinkerton,5,7 Lars Rönnblom,6 Stacey Siu,8 Vanessa Taylor,8 Tiiu Wennberg,2 Dimitrios Zervas,5,7 Arian D J Laurence,9 Suman Mitra,2 Maria G Belvisi,5,7 Mark Birrell,5,7 Annika Borde2 1Medicinal Chemistry, Research and Early Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Gothenburg, Sweden; 2Bioscience, Research and Early Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Gothenburg, Sweden; 3DMPK, Research and Early Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Gothenburg, Sweden; 4Discovery Science, R&D, AstraZeneca, Gothenburg, Sweden; 5Respiratory Pharmacology Group, Division of Airway Disease, National Heart and Lung Institute, Imperial College London, London, UK; 6Rheumatology and Science for Life Laboratories, Department of Medical Sciences, Uppsala University, Uppsala, Sweden; 7Research and Early Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Gothenburg, Sweden; 8Rigel Pharmaceuticals, South San Francisco, CA, USA; 9Department of Haematology, University College London Hospitals NHS Foundation Trust, London, UKCorrespondence: Magnus Nilsson, Medicinal Chemistry, Research and Early Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Gothenburg, SE-431 83, Sweden, Tel +46722237222, Email Magnus.Nilsson@astrazeneca.comPurpose: Janus kinase 1 (JAK1) is implicated in multiple inflammatory pathways that are critical for the pathogenesis of asthma, including the interleukin (IL)-4, IL-5, IL-13, and thymic stromal lymphopoietin cytokine signaling pathways, which have previously been targeted to treat allergic asthma. Here, we describe the development of AZD0449 and AZD4604, two novel and highly selective JAK1 inhibitors with promising properties for inhalation.Methods: The effects of AZD0449 and AZD4604 in JAK1 signaling pathways were assessed by measuring phosphorylation of signal transducer and activator of transcription (STAT) proteins and chemokine release using immunoassays of whole blood from healthy human volunteers and rats. Pharmacokinetic studies performed on rats evaluated AZD0449 at a lung deposited dose of 52 μg/kg and AZD4604 at 30 μg/kg. The efficacy of AZD0449 and AZD4604 was assessed by evaluating lung inflammation (cell count and cytokine levels) and the late asthmatic response (average enhanced pause [Penh]).Results: Both compounds inhibited JAK1-dependent cytokine signaling pathways in a dose-dependent manner in human and rat leukocytes. After intratracheal administration in rats, both compounds exhibited low systemic exposures and medium-to-long terminal lung half-lives (AZD0449, 34 hours; AZD4604, 5 hours). Both compounds inhibited STAT3 and STAT5 phosphorylation in lung tissue from ovalbumin (OVA)-challenged rats. AZD0449 and AZD4604 also inhibited eosinophilia in the lung and reduced the late asthmatic response, measured as Penh in the OVA rat model.Conclusion: AZD0449 and AZD4604 show potential as inhibitors of signaling pathways involved in asthmatic immune responses, with target engagement demonstrated locally in the lung. These findings support the clinical development of AZD0449 and AZD4604 for the treatment of patients with asthma.Keywords: AZD0449, AZD4604, JAK, STAT